(untitled) (Research, Society and Development, 2021)
This work presents an environmental geographical approach directly associated with the use of Geotechnologies as a form of phytomass assessment. This analysis is directed to one of the Conservation Units located in the Pantanal of Mato Grosso do Sul, the Private Reserve of Natural Heritage (RPPN) Fazenda Penha, created in 1997. From the Landsat 5 and Landsat 8 images, the analysis was sought of space - temporal behavior in the period of 29 (twenty-nine) years based on images from the USGS, before and after the creation of the RPPN. The spectral index used was the Normalized Difference Vegetation Index (NDVI), in addition to the multitemporal composition from the results of each year, the multitemporal composition for the red bands and the multitemporal composition for the near infrared bands of each year. The evaluation also involved the study of the surrounding areas, with the generation of shock absorbers of 5,000 meters. the images show the loss of phytomass in the Serra do Amolar region. The same occurred in the vicinity of the Unit. There was less reflectance in the near infrared range and greater reflectance in the red range. It is suggested that in 2016 there was a lower incidence of precipitation or greater evaporation in the region, contributing to a severe drought in the Serra do Amolar and consequently lower NDVI value.